Sovereign bond yields spreads spillovers in the EMU - Afonso, António (2018)
We study the sovereign bond market co-movements and spillovers within 10 EMU countries, the so-called “periphery” and “core” countries, during the period 1999:01 to 2016:07. Implementing Generalized Methods of Moments (GMM) within a panel setting and bivariate VAR analysis, we find that an increase in the lagged spreads of Italian and Austrian bonds negatively affect the spreads of the whole sample while the increase in the Irish, Portuguese, Belgian and French lagged yields increased the overall spreads. In the VAR analysis we find that spillover effects within the sample are mostly positive.